(untitled) (Polish Yearbook of International Law, 2017)
This article is devoted to current practices concerning the application of general principles of law in the light of their function in the international legal system. As a means of the application and interpretation of both treaty and customary law, general principles of law perform a crucial function in the system of international law, which is understood as set of interrelated rules and principles – norms. The role played by general principles of law in the international legal order has been discussed by academia for years now. Initially they were used to ensure the completeness of the system of international law. However, at the current stage of development of international law, when many of them have been codifed, they are usually invoked by international courts for the interpretation of treaties and customary law and/or the determination of their scope. This means that despite their ongoing codifcation they do not lose their character as general principles and are still applied by international courts in the process of judicial argumentation and the interpretation of other norms to which they are pertinent. References by international courts to general principles of law perform the allimportant function of maintaining the coherence of the international legal order, which is faced with the twin challenges of fragmentation and the proliferation of international courts.